Antibiotic Susceptibility Pattern of Corynebacterium diphtheriae Isolated from Outbreaks in Indonesia 2010-2015 - Kambang Sariadji; Sunarno Sunarno; Nelly Puspandari; Masri Sembiring (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Diptheria cases are treated with both anti-diphtheria serum (ADS) and antibiotics. Penicillin and erythromycin are the primary choices for any Corynebacterium diphtheriae (C. diphtheriae) infection. Antibiotic susceptibility pattern of C. diphtheriae has not been reported in Indonesia since 1982. The improper use of antibiotics, as well as, the consumption of antibiotics without prescription, will increase the resistance of C. diphtheriae. This study aims to determine the susceptibility pattern and the effectiveness of C. diphtheriae to several antibiotics.METHODS: A total of 57 C. diphtheriae isolates were recultured by using Blood Agar (BA) and Cystine Tellurite Blood Agar (CTBA). Afterward, these isolates were identified by using API Coryne. The antibiotic susceptibility pattern was determined by using Kirby Bauer Method based on CLSI M45-A2.RESULTS: These studies revealed that as the primary choice of diphtheria cases, 10.5% of C. diphtheriae isolates were resistant to Penicillin and 5.3% were resistant to erythromycin. Seven isolates (12%) showed resistance to more than one antibiotics, such as tetracycline and clindamycin, vancomycin and clindamycin, penicillin and tetracycline, also penicillin and vancomycin. Moreover, 4 isolates (7%) were resistant to 3-5 antibiotics. All isolates were susceptible to moxifloxacin and linezolid.CONCLUSION: Some C. diphtheriae isolates were resistant to penicillin and erythromycin, which are known as the primary choice for the treatment of C. diphtheriae infection. Even though, all isolates susceptible to moxifloxacin and linezolid.KEYWORDS: Corynebacterium diphtheriae, resistance, antimicrobial